THE USE OF ARABIC LANGUAGE PODCASTS TO IMPROVE MAHARAH ISTIMA' - Haris Hasanuddin Uddin (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2026)
ABSTRACTListening comprehension is an important basic skill in Arabic language learning because it serves as the foundation for mastering other language skills. However, the process of teaching listening comprehension often faces various obstacles, such as a limited supply of authentic audio materials, low motivation to learn, and a lack of variety in teaching methods. This article aims to examine the use of podcasts as a learning medium to improve students’ listening skills. This study employs a literature review method by analyzing various scientific sources (including journals, articles, and previous studies) relevant to the use of podcasts in Arabic language learning. The results of the study indicate that podcasts have significant potential to improve listening skills because they provide authentic, flexible, and easily accessible audio materials, and are capable of enhancing students’ vocabulary mastery, contextual language comprehension, and learning motivation. However, there are several challenges in their implementation, such as the diversity of Arabic dialects, limited access to technology, and a lack of direct interaction with instructors. Therefore, the use of podcasts needs to be integrated with appropriate learning strategies to achieve optimal results in developing listening skills.Keywords: Podcasts, Listening Skills, Arabic Language Learning, Learning Media, Literature Review.